ICHTHYO-FAUNA OF RIVER CHAMBAL IN MADHYA PRADESH - RIDHI, Ms; JHA, B. C.; PARASHAR, A.; DAS, A. K.; BOSE, ARUN KUMAR (Journal of the Inland Fisheries Society of India, 2021)
River Chambal is an important tributary of river Yamuna which drains the states of Madhya Pradesh, Rajasthan and Uttar Pradesh. The total length of the river is estimated at 965 km and is the largest in western Madhya Pradesh. A number of ichthyologists have studied the fish diversity of central India including Madhya Pradesh (Saxena et al., 2005; Lakra and Sarkar, 2007; Sharma, 2007; Heda, 2009; Vyas et al., 2009; Lakara et al., 2010; Vyas et al., 2012; Sarkar et al., 2012; Bose et al., 2012). In recent years, however, the natural fish diversity is declining due to wanton killing of juveniles and brooders, aquatic pollution, excessive water abstraction and habitat destruction, indiscriminate or unintentional introduction of exotics etc. (Saxena et al., 2005). Effective conservation and judicious exploitation of resources would be critical in protecting the fish diversity. Poor database, however, is an impediment in drawing suitable conservation or management norms and need attention. The present work aims to assess the fish diversity of river Chambal in Madhya Pradesh, which hitherto remains under-explored in this regard.